2017
DOI: 10.1016/j.engstruct.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Shear behaviour of recycled aggregate concrete beams with and without shear reinforcement

Abstract: An experimental study of the shear behavior of recycled aggregate concrete (RAC) beams with and without shear reinforcement is presented. Nine full-scale simply supported beams were loaded in fourpoint bending tests until failure. Three different replacement ratios of coarse natural with coarse recycled concrete aggregate (0%, 50%, and 100 %), and three different shear reinforcement ratios (0%, 0.14%, and 0.19 %) were the main parameters. All natural aggregate concretes (NAC) and recycled aggregate concretes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 19 publications
7
60
0
Order By: Relevance
“…Adding 8% silica fume in the weight of the cement to the recycled aggregate concrete could improve the shear cracking of reinforced recycled aggregate concrete beams, while the ultimate loads tend to be the same [34]. When the concrete with coarse recycled aggregate replacing 50% and 100% natural aggregate has similar compressive strength of conventional concrete, the shear behavior and shear strength of reinforced recycled aggregate concrete beams with stirrups ratio of 0.14% and 0.19% were very similar to that of the corresponding reinforced conventional concrete beams [35]. By treating the recycled aggregate as two-phase material comprising residual mortar and natural aggregate, the shear performance of reinforced recycled aggregate concrete beams is comparable, or even superior, to that of beams made entirely with natural aggregate [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding 8% silica fume in the weight of the cement to the recycled aggregate concrete could improve the shear cracking of reinforced recycled aggregate concrete beams, while the ultimate loads tend to be the same [34]. When the concrete with coarse recycled aggregate replacing 50% and 100% natural aggregate has similar compressive strength of conventional concrete, the shear behavior and shear strength of reinforced recycled aggregate concrete beams with stirrups ratio of 0.14% and 0.19% were very similar to that of the corresponding reinforced conventional concrete beams [35]. By treating the recycled aggregate as two-phase material comprising residual mortar and natural aggregate, the shear performance of reinforced recycled aggregate concrete beams is comparable, or even superior, to that of beams made entirely with natural aggregate [36].…”
Section: Introductionmentioning
confidence: 99%
“…By treating the recycled aggregate as two-phase material comprising residual mortar and natural aggregate, the shear performance of reinforced recycled aggregate concrete beams is comparable, or even superior, to that of beams made entirely with natural aggregate [36]. Generally, the tested recycled aggregate concrete beams could be designed conservatively by using the current codes for conventional concrete beam [31,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the code equations can adequately predict the shear strength of recycled coarse aggregate concrete beams. Ignjatović et al [9] conducted 9 experiments to study the shear behaviour of recycled aggregate concrete beams with and without shear reinforcement. The results showed that the shear strength of the beams with 50% and 100% of recycled concrete aggregate were very similar to that of the corresponding beam with natural aggregate.…”
Section: Literature Searchmentioning
confidence: 99%
“…In the first case, the truss model, presented by Ritter and later developed by Mörsch, is one of most accepted theories to explain the behavior of concrete beams with shear reinforcement. However, the behavior of concrete beams without shear reinforcement remains a current topic, and studies have been published within the framework of safety of existing structure or related to the use or recycled aggregate concrete . The parameters that contributes for shear transfer mechanisms are identified as follows: transverse reinforcement (this component does not exist in beams without stirrups); dowel action of the longitudinal reinforcement ( V d ); crack friction or aggregate interlock ( V ag ); shear stresses on uncracked concrete in compressive zone ( V c ); and arch effect (particularly, relevant in short span beams with loads applied near supports, where a flow of compression stresses is directly formed to the support).…”
Section: Introductionmentioning
confidence: 99%
“…However, the behavior of concrete beams without shear reinforcement remains a current topic, and studies have been published within the framework of safety of existing structure or related to the use or recycled aggregate concrete. [4][5][6][7] The parameters that contributes for shear transfer mechanisms are identified as follows: transverse Discussion on this paper must be submitted within two months of the print publication. The discussion will then be published in print, along with the authors' closure, if any, approximately nine months after the print publication.…”
Section: Introductionmentioning
confidence: 99%